CMC-based hydrogels loaded with Hypericum perforatum nanoemulsion for potential wound dressing applications. (July 2022) - Moradi, Mina; Barati, Aboulfazl; Moradi, Sara; Arjomandzadegan, Mohammad
Wound healing is a complicated process requiring appropriate environment to accelerate healing process. In the recent years, many wound dressings have been developed for treating various kinds of wounds. In this study, we aimed to develop a novel dressing with high ability of burn wound healing and minimum side effects. Carboxymethyl cellulose (CMC) based hydrogels containing Hypericum perforatum were developed by grafting methacrylic acid and acrylamide onto CMC to produce a good mechanical strength dressing. Covalent crosslinking, which is responsible for stable mechanical structure, led to a 3D structure with appropriate water vapor transmission rate (2950 g/m 2 /day), controlled drug release (33% in 78 h), and great burn healing ability (almost complete healing in 10 day). The hydrogel has proper antimicrobial activity against the tested microorganisms. Zone of inhibition against E.coli was the higher in comparison with S. aureus and Candida . Minimum inhibitory concentration (MIC) for C. albicans, S. aureus, and E. coli were as 6, 4, and 5 mg/ml of H. perforatum . In vivo experiments on rats revealed that wound healing process by loaded hydrogels was faster in comparison with control group. All the results indicated that prepared hydrogel has the capability to accelerate burn wound healing process.